Freezing tolerance in grasses along an altitudinal gradient in the Venezuelan Andes - Márquez, Edjuly J.; Rada R., Fermin J.; Fariñas G, Mario R. (SABER ULA, 2006)
Freezing tolerance in grasses along an altitudinal gradient in the Venezuelan Andes (Márquez, Edjuly J., Rada, Fermín y Fariñas, Mario) Abstract The tropical high Andes experience greater daily temperature oscillations compared to seasonal ones as well as a high frequency of night frost occurrence year round. Survival of organisms, under such environmental conditions, has been determined by selective forces which have evolved into adaptations including avoidance or tolerance to freezing. These adaptations have been studied in diVerent species of trees, shrubs and perennial herbs in páramo ecosystems, while they have not been considered in grasses, an important family of the páramo. In order to understand survival of Poaceae, resistance mechanisms were determined. The study was performed along an altitudinal gradient (2,500-4,200 m a.s.l.) in the páramo. Supercooling capacity and frost injury temperature were determined in nine species in order to establish cold resistance mechanisms. Grasses registered a very low supercooling capacity along the altitudinal gradient, with ice formation between - 6 and - 3°C. On the other hand, frost injury temperature oscillated between - 18 and - 7°C. Our results suggest that grasses exhibit freezing tolerance as their main cold resistance mechanism. Since grasses grow at ground level, where greatest heat loss takes place, tolerance may be related to this life form as reported for other small life forms. Artículo publicado por web en:SpringerVerlag. Oecologia. Volumen 150. Number 3 / December, 2006. http://springerlink.metapress.com/content/h17755k90613/?p=2e54f7bf0caa4009a8edca94d9373cf2&pi=0
Keywords: Facultad de Ciencias.; Instituto de Ciencias Ambientales y Ecológicas (ICAE); Injury temperature; Supercooling capacity; Tropical high Andes; Poaceae; Artículos